Band-bending induced passivation: high performance and stable perovskite solar cells using a perhydropoly(silazane) precursor. Issue 4 (20th November 2019) - Kanda, Hiroyuki; Shibayama, Naoyuki; Huckaba, Aron Joel; Lee, Yonghui; Paek, Sanghyun; Klipfel, Nadja; Roldán-Carmona, Cristina; Queloz, Valentin Ianis Emmanuel; Grancini, Giulia; Zhang, Yi; Abuhelaiqa, Mousa; Cho, Kyung Taek; et al.
Abstract : It could successfully control the band-bending of the perovskite semiconductor, which led to improvement of the photovoltaic performance. Abstract : Surface passivation of the perovskite photo absorber is a key factor to improve the photovoltaic performance. So far robust passivation strategies have not yet been revealed. Here, we demonstrate a successful passivation strategy which controls the Fermi-level of the perovskite surface by improving the surface states. Such Fermi-level control caused band-bending between the surface and bulk of the perovskite, which enhanced the hole-extraction from the absorber bulk to the HTM side. As an added benefit, the inorganic passivation layer improved the device light stability. By depositing a thick protection layer on the complete device, a remarkable waterproofing effect was obtained. As a result, an enhancement of V OC and the conversion efficiency from 20.5% to 22.1% was achieved. We revealed these passivation mechanisms and used perhydropoly(silazane) (PHPS) derived silica to control the perovskite surface states.